2014
DOI: 10.1186/s12883-014-0155-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, lifestyle, socioeconomic determinants and rate of asymptomatic intracranial atherosclerosis in stroke free Pakistanis

Abstract: BackgroundIntracranial Atherosclerotic Disease (ICAD) is the most frequent etiology of stroke with high prevalence among Asians. Despite this, early determinants of ICAD have not been described from this region.MethodsThe study is an analytical prospective cross-sectional study of 200 adults from Radiology Departments of two diagnostic centers in Karachi. Eligible participants confirmed the absence of stroke symptoms via the Questionnaire for Verifying Stroke Free Status (QVSFS) and underwent an interview cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
1
13
0
Order By: Relevance
“…However, they found no association between intracranial atherosclerosis and low ABI in the stroke patients, and hence suggested that a low ABI could be a predictor for ECAS but not ICAS. As expected, it was found that people with ACCS are older and have more vascular-related risk factors, similar to the reports from the other two studies [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…However, they found no association between intracranial atherosclerosis and low ABI in the stroke patients, and hence suggested that a low ABI could be a predictor for ECAS but not ICAS. As expected, it was found that people with ACCS are older and have more vascular-related risk factors, similar to the reports from the other two studies [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…Age, gender, educational status, occupation, marital status, family status was reported as demographic data. For socioeconomic indicators, World Bank Wealth index questionnaire was adopted [20]. Stroke survivors Medical complications, Post-stroke complications were noted at the time of interview [21] and stroke sub-types were evaluated through medical reports [22].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the risk of stroke seems to have a continuous association with blood pressure down to levels as low as 115/75 mmHg [61]. In light of this, the national guidelines redefined categories of hypertension so that normal systolic blood pressure is < 120 mmHg and normal diastolic blood pressure is < 80 mmHg [66]. Most recently, it has been suggested that variability in blood pressure measurements (visit to visit, distinct measurements within a given visit) are associated with greater risk of stroke [67].…”
Section: Preventable Life Style Risk Factorsmentioning
confidence: 99%